MECHANICAL PROPERTIES OF THICK AND THIN AA1100 WELDED USING BOBBIN FRICTION STIR WELDING - Kassim, M.K.A.M.; Sued, M.K.; Pons, D.J. (Journal of Advanced Manufacturing Technology (JAMT), 2019)
This study is to investigate the mechanical properties of thick and thin material welded using Bobbin Friction Stir Welding technique. The material that used for this study was Aluminium Alloy 1100 with the thickness of 3mm and 6mm. The aim of this study is to identify the process sensitivity for different material thickness. Different tapered shoulder was tested in this study and the spindle speed and welding speed were varied. There are two sets of parameters used which are 900 rpm and 310 mm/min; and 1440 rpm and 190 mm/min for spindle speed and welding speed respectively. The welding process was done by CNC Milling Machine. The welded products were tested using tensile test, micro hardness, and XRD analysis. The result shows that low spindle speed and higher travel speed produce good weld. This only can be produced with small tapered angle on the shoulder of the tool that represents the best tapered angle used in this study. If not, defect such as open tunnel, teared material at tool entry and void will be produced. However, the welding for thin materials is challenging and for different material thickness, optimized parameter should be used for high strength weld.